2011
DOI: 10.1074/jbc.m111.245985
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Ameliorates Doxorubicin-induced Cardiotoxicity through Akt Protein-dependent Mechanism

Abstract: Accumulating evidence shows that obesity is associated with doxorubicin cardiac toxicity in the heart, but the molecular mechanisms that contribute to this pathological response are not understood. Adiponectin is an adipose-derived, cardioprotective factor that is down-regulated in obesity. Here, we investigated the effect of adiponectin on doxorubicin (DOX)-induced cardiotoxicity and assessed the mechanisms of this effect. A single dose of DOX was intraperitoneally injected into the abdomen of adiponectin kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…Conversely, overexpression of adiponectin improves left ventricular hypertrophy, diastolic dysfunction and myocardial oxidative stress in response to aldosterone infusion 36) . We have also demonstrated that adiponectin prevents doxorubicin-induced cardiotoxicity through its ability to stimulate myocyte survival 37) . Overall, adiponectin acts as an adipocytokine that protects against the development of various heart diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Conversely, overexpression of adiponectin improves left ventricular hypertrophy, diastolic dysfunction and myocardial oxidative stress in response to aldosterone infusion 36) . We have also demonstrated that adiponectin prevents doxorubicin-induced cardiotoxicity through its ability to stimulate myocyte survival 37) . Overall, adiponectin acts as an adipocytokine that protects against the development of various heart diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Although exercise training has previously been shown to increase Akt phosphorylation (3), the role of Akt in DOX cardiotoxicity is less clear. While some studies have shown DOX decreases Akt phosphorylation, others have observed elevated Akt activity in vivo (6,11,25). Because many factors influence Akt phosphorylation, it appears the experimental model is very important for interpretation of Akt activity.…”
Section: Sed+dox Ex+dox Ex Dox (-) (+) (-) (+) (-) (+) (-) (+) (-) (+mentioning
confidence: 99%
“…64 Adiponectin-KO mice showed exacerbated left ventricle contractile dysfunction after doxorubicin injection, whereas exogenous adiponectin improved doxorubicin-induced left ventricular dysfunction in wild-type and adiponectin-KO mice. 62 However, no study has yet been performed to elucidate the role of adiponectin on trastuzumab-induced cardiac dysfunction.…”
Section: Obesity and Cardiotoxicitymentioning
confidence: 99%
“…60 Mechanisms by which overweight or obesity is able to promote anthracycline-induced cardiotoxicity may involve adiponectin downregulation. 61,62 The dysregulation of adipocyte-derived hormones, adipocytokines, promotes the development of diverse obesity-linked diseases. 63 Plasma adiponectin levels are decreased in obese patients.…”
Section: Obesity and Cardiotoxicitymentioning
confidence: 99%